SCNN1A expression in triple-negative breast cancer: clinical implications for prognosis and neoadjuvant therapy response - Xin Jin; Yue Ge; Tongjun Sun; Yunfei Ma; Yan Zhao; Qiang Xie; Faxiang Yin; Ligong Zhang; Jun Qian (World Journal of Surgical Oncology)
Abstract Background This study aimed to identify differential genes between pathological complete response (pCR) and non-pCR following neoadjuvant chemotherapy in triple-negative breast cancer (TNBC). Additionally, the expression and clinical significance of the differential gene SCNN1A in TNBC were explored. Methods Differential genes related to prognosis following neoadjuvant chemotherapy in TNBC were identified using the GEO database. Core genes were selected through the Cytoscape visualization and support vector machine (SVM) feature selection. The prognostic significance of these genes was assessed via online databases. SCNN1A expression and its correlation with clinicopathological data and neoadjuvant chemotherapy response were analyzed in 283 TNBC patients from the First Affiliated Hospital of Bengbu Medical University using immunohistochemistry. Results Eleven core genes, including SCNN1A, were identified from 912 differential genes. High SCNN1A expression was associated with poor prognosis in TNBC patients via online database analysis. Gene set difference analysis (GSVA) and Gene set enrichment analysis (GSEA) revealed that SCNN1A was involved in several metabolic pathways. The clinical data indicated that high SCNN1A expression was associated with advanced T (p = 0.037) and N stages (p = 0.011), but not with age, HER2 status, Ki-67 expression, or histological grade. High SCNN1A expression was significantly more frequent in non-pCR patients compared to pCR patients, and high SCNN1A expression was associated with significantly lower overall survival (OS) and disease-free survival (DFS). Conclusion SCNN1A overexpression is associated with poor prognosis and non-pCR status in TNBC patients undergoing neoadjuvant chemotherapy.